ESG Performance and Bank Soundness in Indonesia: Evidence from Conventional and Islamic Banks - Rinda Siaga Pangestuti; Raymond Raymond; Joel Imanuel Gustian; Patrialis Ardy Kusuma (International Forum of Researchers and Lecturers, 2026)
This study examines the relationship between environmental, social, and governance (ESG) performance and bank soundness in Indonesia during 2020–2025, a period marked by rapid expansion of sustainable-finance disclosure. Based on stakeholder, legitimacy, and risk-management theories, this research analyzes the influence of ESG performance, bank size, and capital adequacy on bank soundness. The study uses an unbalanced panel dataset of 23 Indonesian banks, consisting of 19 conventional and 4 Islamic banks, with 138 bank-year observations obtained from LSEG/Refinitiv Datastream. The analysis employs static panel regression with return on assets (ROA) as the dependent variable and applies model selection tests, including Chow, Breusch–Pagan Lagrange-Multiplier, and Hausman tests. The findings indicate that ESG performance has a positive but insignificant relationship with bank soundness, while bank size shows a more consistent positive effect. Capital adequacy does not demonstrate a significant influence. Robustness tests using alternative indicators confirm that ESG effects remain directionally positive but statistically limited. The study concludes that the ESG–soundness relationship in Indonesian banking remains inconclusive, while institutional scale continues to be a stronger determinant of bank performance.